An unusual progressive stridor - Apraxine, Matveï (Breathe (Sheff), 2020)
A flow–volume curve with a flattening of the inspiratory and expiratory limb suggests a proximal obstruction of the upper airways. Plasma cell neoplasms need to be considered in the differential diagnosis of an invasion of the upper respiratory tract. https://bit.ly/2K9lOXj